Nilai Jasa Fauna sebagai Komponen Ekosistem di Taman Nasional Baluran - Joko Mulyo Ichtiarso (Fakultas Kehutanan Universitas Winaya Mukti, 2020)
The benefit of ecosystem services are the completeness of the outputs resulting from biological, physical, chemical, and socio-cultural processes in the forest that are useful for human life and environment. The object of research is to know how much the economic value of fauna in ecosystem services which has been utilized by the community buffer village and the dependence on Baluran National Park (BNP). Method of research by quantitative and qualitative analysis. Data collected are typological conditions of BNP community buffer village, human resources who used the services of BNP ecosystem services, identity of community who used ecosystem services, types of ecosystem services used by community, harvest season, location of ecosystem services, community income that uses ecosystem and dependence on BNP ecosystem services. The result of research are economic value of the services of fauna that ecosystem components of BNP that have been used by buffer community village and dependence on BNP have form of forest honey (Rp. 1,073,332,000), kroto (Rp. 784,665,000), and snails (Rp. 648,080). Total economic value of fauna that ecosystem component of BNP is Rp. 2,506,077,000,- per year